Answer:
A, D, E
Step-by-step explanation:
AREA OF SQUARE
[tex](x - 1)(x - 1) = x^2 - 2x + 1[/tex]
AREA OF RECTANGLE
[tex]x(x - 2) = x^2 - 2x[/tex]
Using this we know that the difference is 1, so B is incorrect. We also know that D and E are correct because we solved for the area. C is also wrong, by the same reasoning. Now, all we need to see is if A is right. Plug in x = 2.
[tex](2)^2 - 2(2) + 1 \\= 4 - 4 + 1 \\= 1[/tex]
Because the area of the square is a square unit larger than the rectangle, the rectangle would have an area of 0, which is impossible, so A is correct.